The role of estradiol metabolism in urogenital schistosomiasis-induced bladder cancer - Nuno Vale; Maria J Gouveia; Gabriel Rinaldi; Júlio Santos; Lúcio Lara Santos; Paul J Brindley; José M Correia da Costa (Tumor Biology, 2017)
Urogenital schistosomiasis is a neglected tropical disease that can lead to bladder cancer. How urogenital schistosomiasis induces carcinogenesis remains unclear, although there is evidence that the human blood fluke Schistosoma haematobium , the infectious agent of urogenital schistosomiasis, releases estradiol-like metabolites. These kind of compounds have been implicated in other cancers. Aiming for enhanced understanding of the pathogenesis of the urogenital schistosomiasis-induced bladder cancer, here we review, interpret, and discuss findings of estradiol-like metabolites detected in both the parasite and in the human urine during urogenital schistosomiasis. Moreover, we predict pathways and enzymes that are involved in the production of these metabolites emphasizing their potential effects on the dysregulation of the tumor suppressor gene p53 expression during urogenital schistosomiasis. Enhanced understanding of these potential carcinogens may not only shed light on urogenital schistosomiasis-induced neoplasia of the bladder, but would also facilitate development of interventions and biomarkers for this and other infection-associated cancers at large.